Living in a Disadvantaged Neighborhood Affects Neural Processing of Facial Trustworthiness - Chang, Shou-An A.; Baskin-Sommers, Arielle (Frontiers in Psychology, 2020)
Neighborhood disorder (i.e., physical or social decay) is associated with decreased trust, which reinforces criminal behavior for some individuals in these communities. However, past research largely is descriptive and has not measured processes underlying trust. Using behavioral and neural (using the late positive potential [LPP], a marker of salience elaboration) indices in a sample of adults (N=55), we examined the association between perceived neighborhood disorder and facial trustworthiness perception as well as the potential moderating role of trustworthiness perception on the association between PND and criminal behavior. Individuals with higher perceived neighborhood disorder displayed less LPP differentiation between untrustworthy and trustworthy faces. Moreover, individuals with higher perceived neighborhood disorder and less LPP differentiation were less likely to commit a variety of crimes, whereas those with higher perceptions of neighborhood disorder and high LPP differentiation were more likely to commit a variety of crimes. Combined, these findings suggest that similarly processing trustworthy and untrustworthy faces, as indexed by less LPP differentiation, may reflect an adaptation among those with higher perceived neighborhood disorder that mitigates against deviant behavior and contacts with the law. Understanding the intersection between neighborhood characteristics and individual-level cognitive-affective processing may provide insight into what shapes beliefs and behaviors about important social information.